KONTRIBUSI MASYARAKAT PESISIR PANTAI PADANG MENATA PEMUKIMANNYA DALAM MENINGKATKAN DAYA TARIK OBJEK WISATA PANTAI PADANG, KOTA PADANG - Febby Fitri Yolanda; Helfia Edial (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to determine: 1) Community contribution in overcoming inadequate environmental infrastructure, 2) Community contribution in overcoming bad house arrangement and environmental public facilities, 3) Community contribution in overcoming unattractive building façade models. This type of research is classified as Mix Methods. The population of this research is the people of RT 004 Rimbo Kaluang sub-district with a total population of 90 households with 73 subjects. Collecting data using questionnaires, documentation and interviews. The data analysis used was two approaches, namely qualitative and quantitative approaches. The results of this study indicate that in order to overcome inadequate environmental infrastructure, the community will repair it together through community contributions, or ask for assistance to Musrembang which is submitted to the village head office. To overcome the poor arrangement of houses and public facilities, there is still no contribution from the community, because the community only contributes to improving the economy, namely by building stalls to sell. To overcome the unattractive building facade model, the community also contributes less because the status of the land there is illegal, so the community builds just for an emergency and does not meet proper housing standards.